Strategy safari : the complete guide through the wilds of strategic management - Mintzberg, Henry; Ahlstrand, Bruce W.; Lampel, Joseph (Harlow : Financial Times Prentice Hall, 2009)
Strategy is the most prestigious but also the most confusing part of business. Managers are constantly bombarded with new jargon and the latest fads promising the magic bullet for every strategic problem. The world of strategy can seem to be an impenetrable jungle. Strategy Safari presents a powerful antidote to the dilemma of needing to know about strategy and yet not being able to find any comprehensible guidelines. This revised edition is a comprehensive, colourful and illuminating tour through the wilds of strategic management.
'And over here, ladies and gentlemen : the strategic management beast' -- The design school : strategy formation as a process of conception -- The planning school : strategy formation as a formal process -- The positioning school : strategy formation as an analytical process -- The entrepreneurial school : strategy formation as a visionary process -- The cognitive school strategy formation as a mental process -- The learning school : strategy formation as an emergent process -- The power school : strategy formation as a process of negotiation -- The cultural school : strategy formation as a collective process -- The environmental school : strategy formation as a reactive process -- The configuration school : strategy formation as a process of transformation -- 'Hang on, ladies and gentlemen, you have yet to meet the whole beast'.
Includes bibliographical references (p. [397]-431) and index.
1
Keywords: Strategic planning; Business planning